Assessing Persian translation of selected rhetorical figures in Venus and Adonis and The Rape of Lucrece by Shakespeare - Abolfazl Horri (مطالعات زبانی و بلاغی)
Rhetorical figures are the artistic use of language that, through the selection of specific linguistic and grammatical structures, assist poets in expressing their ideas and thoughts. These figures are highly structure-oriented and are lost in translation to another language. The loss of literary devices in the translation of poetic texts becomes even more perplexing because, in poetry, not only the meaning but also the form is important. And, since what is lost most in the translation of poetic language is the form, it is clear that poetic devices are also lost to a great extent. However, there are translators who are fully aware of the style, context, and form of both source and target languages and skillfully recreate these specific forms in the target language. Among English poets, Shakespeare has ingeniously and efficiently used literary devices in his theatrical and poetic works. Among Shakespeare's non-theatrical works, the two poems Venus and Adonis and The Rape of Lucrece, which have recently been translated into Persian, have significantly utilized literary devices. A general evaluation of the Persian translation of these selected devices in these two poems, based on functional equivalence, shows that the Persian translator has made great effort to translate these devices into Persian in an efficient manner and within the framework of a functional equivalence. This article aims to examine and evaluate a selected number of these devices in the Persian translation of the two poems within the framework of functional equivalence.